Intra- and postoperative relative angiotensin II deficiency in patients undergoing elective major abdominal surgery - Krenn, Katharina; Höbart, Petra; Adam, Lukas; Riemann, Gregor; Christiansen, Finn; Domenig, Oliver; Ullrich, Roman (Frontiers in Endocrinology, 2024)
T he classical axis of the renin-angiotensin system (RAS) makes an important contribution to blood pressure regulation under general anesthesia via the vasopressor angiotensin (Ang) II. As part of the alternative RAS, angiotensin -converting enzyme (ACE) 2 modulates the proinflammatory and fibrotic effects of Ang II by processing it into the organprotective Ang 1-7 that is cleaved to Ang 1-5 by ACE. Although ACE2 levels may be associated with postoperative complications, alternative RAS metabolites have never been studied perioperatively. This study was designed to investigate the perioperative kinetics and balance of both RAS axes around major abdominal surgery. Methods: In this observational cohort study, we included 35 patients undergoing elective major abdominal surgery and performed blood sampling before and after induction of anesthesia, one hour after skin incision, at the end of surgery, and on postoperative days (POD) 1, 3, and 7. Equilibrium concentrations of Ang I-IV, Ang 1-7 and Ang 1-5 in plasma were quantified using mass spectrometry. ACE and ACE2 plasma protein levels were measured with ELISA. Results: Surgery caused a rapid, transient, and primarily renin-dependent activation of both RAS axes that returned to baseline on the first POD, followed by suppression. After induction, the Ang II/Ang I ratio persistently decreased, while ACE levels started to increase on the first POD (all P <0.01 versus before anesthesia). Conversely, ACE2 levels increased on the third and seventh POD (both P <0.001 versus before anesthesia), when median Ang 1-7 concentrations were unquantifiably low. Discussion: The postoperative ACE2 elevation may prolong the decrease of the Ang II/Ang I ratio by increased processing of Ang II. Further clarification of intraoperative factors leading to relative Ang II deficiency and sources of postoperatively elevated ACE2 is warranted.